2021
DOI: 10.3390/educsci11110693
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Predictors of Students’ Emergency Remote Online Learning Satisfaction during COVID-19

Abstract: In order not to lose continuity in education during COVID-19, universities mainly found the solution in Emergency remote teaching. Student satisfaction with online learning experience is one of the measures of the excellence of learning practice. Our goal was to test the hypothesis that the predictors of students’ satisfaction with emergency remote online learning are their prior experience, attitude toward online learning, their motivation, aspects of the learning situation they value (expectations), and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 50 publications
(120 reference statements)
3
23
1
4
Order By: Relevance
“…The precarious roles that instructors had to take amid the pandemic were a reflection of students' diverse expectations and demands during the crisis. Studies on students' ERT experiences have been conducted in many parts of the world [4][5][6][7][8][9][10][11]. These findings overall suggest how various factors-both in-and inter-dependently-shaped students' learning.…”
Section: Ert During the Covid-19 Pandemicmentioning
confidence: 85%
See 2 more Smart Citations
“…The precarious roles that instructors had to take amid the pandemic were a reflection of students' diverse expectations and demands during the crisis. Studies on students' ERT experiences have been conducted in many parts of the world [4][5][6][7][8][9][10][11]. These findings overall suggest how various factors-both in-and inter-dependently-shaped students' learning.…”
Section: Ert During the Covid-19 Pandemicmentioning
confidence: 85%
“…One of the most explored are factors that smoothened students' ERT experiences. In Kovačević et al's [6] survey research on university students in Serbia, previous online learning experience and familiarity with learning platforms were the predictors of students' learning satisfaction. On the contrary, Poláková and Klímová [8] found in their survey that participating students in Slovakia did not consider lack of experience with online learning hindered their learning.…”
Section: Ert During the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer self-efficacy, referred by some authors as technological self-efficacy [16], technological pedagogical knowledge (TPK) self-efficacy [8] and digital literacy [33] refers to all those skills, attitudes and knowledge required by teachers in a digitalized world. It also refers to the belief in one's capability to organise and execute internet-related actions required to accomplish assigned tasks [34]. If university teachers have strong ICT-related knowledge, they will be able to overcome ICT related barriers and thus successfully incorporate technology into their teaching practice [33,35].…”
Section: Methodsmentioning
confidence: 99%
“…The concern about teacher fear in the use of ICT is confirmed by [50], who indicated that even though some teachers believe in constructivist pedagogy, they are still reluctant to use technology because of various constraints such as lack of adequate time to design lessons for online delivery, insufficient specialized help, absence of physical contact with students as well as challenges related to internet connectivity. [34] advise that factors that should be taken into consideration, besides the teaching process and instructional content, are e-competencies of students and educators, as well as the attitudes toward this mode of learning and the usability of the system. In this study, the opportunities provided by the e-learning system to save the academic year through moving to online teaching and learning to mitigate the effects of COVID-19 in face-to-face tuition seems to have cultivated positive attitudes towards use.…”
mentioning
confidence: 99%